CREDIT GUARANTEE FOR SMALL AND MEDIUM ENTERPRISES THE CASE OF MUNICIPAL CREDIT GUARANTEE FUNDS IN VIETNAM - Dao, Ha Thi Thieu (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
Only 23 out of 63 provinces in Vietnam have established credit guarantee funds since 2001, when Vietnamese government encouraged the establishment of provincial credit guarantee funds to support small and medium enterprises. The Credit Guarantee Fund which reach the largest small and medium enterprises guarantee for only 105 loans. The article uses content analysis method to assess the situation of credit guarantee operation for small and medium enterprises in Vietnam. Research shows that guarantee funds are currently not expanding due to the fact that unfavorable guarantee regulations do not encourage borrowing under the guarantee of these funds; charter capital is at small scale; cooperation between banks and these funds are not based on sharing benefits and risks; inflexible and increative Municipal Credit Guarantee Funds. Following the recent findings, the paper suggests recommendations for the policies to strengthen the credit accessibility of SMEs in Vietnam.